MBR technology: A practical approach for petrochemical wastewater treatment. (1st February 2017) - Sadeghi, Fatemeh; Mehrnia, Mohammad Reza; Nabizadeh, Ramin; Bahadori, Mohammad Bagher; Sarrafzadeh, Mohammad Hossein
ABSTRACT: In this research membrane bioreactor (MBR) technology as a novel and practical technology was studied for treatment of saline petrochemical wastewater. Membrane fouling and permeability, mixed liquor properties such as change of flock size, and effluent characteristics of MBR were measured in presence of various salt concentrations in the feed. The results showed that the increasing the salinity reduced cake layer, total membrane resistances and increased the membrane permeability and sludge particle size. Also, COD removal efficiencies were up to 91% in all trials. These results indicate that the MBR was highly efficient for treating saline petrochemical wastewater.